A Gut Feeling in Amyotrophic Lateral Sclerosis: Microbiome of Mice and Men - Martin, Sarah; Battistini, Carolina; Sun, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Amyotrophic lateral sclerosis (ALS) is a severely debilitating disease characterized by progressive degeneration of motor neurons. ALS etiology and pathophysiology are not well understood. It could be the consequences of complex interactions among host factors, microbiome, and the environmental factors. Recent data suggest the novel roles of intestinal dysfunction and microbiota in ALS etiology and progression. Although microbiome may indeed play a critical role in ALS pathogenesis, studies implicating innate immunity and intestinal changes in early disease pathology are limited. The gastrointestinal symptoms in the ALS patients before their diagnosis are largely ignored in the current medical practice. This review aims to explore existing evidence of gastrointestinal symptoms and progress of microbiome in ALS pathogenesis from human and animal studies. We discuss dietary, metabolites, and possible therapeutic approaches by targeting intestinal function and microbiome. Finally, we evaluate existing evidence and identify gaps in the knowledge for future directions in ALS. It is essential to understanding the microbiome and intestinal pathogenesis that determine when, where, and whether microbiome and metabolites critical to ALS progression. These studies will help us to develop more accurate diagnosis and better treatment not only for this challenging disease, but also for other neurodegenerative diseases.